Knowledge and Attitude in First Aid for Traffic Accident - Pratama, Aditya; Nirmalasari, Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Traffic accidents are a worldwide issue. Actions to prevent morbidity and mortality in accident victims are required to reduce the rate of mortality. The community's knowledge, attitude, and skill in providing first aid are needed to decrease this quantity. Objective: This research aimed to describe the knowledge and attitude of the community on first aid in traffic accidents in Patalan, Jetis, Bantul, Yogyakarta. Methods: This research was a descriptive study with a cross-sectional approach. The sample of this study was 49 respondents who used nonprobability sampling with a purposive sampling technique. Data was collected using the knowledge and attitude questionnaire. The data were analyzed using univariate analysis with frequency distribution and percentage. Results: The results of this research show that most of the respondents were male (53,1%), ages 26-35 years old (30.6%), high school/vocational education (67%). The community received information sources (63.3%), and 28.6% received information from counseling. Furthermore, most respondents (59.2%) have never assisted traffic accident victims. The respondents' knowledge is moderate (83.7%), and their attitude about first aid is positive (71.4%). Conclusion: Most of the community has moderate knowledge and a positive attitude about first aid for traffic accidents.